Evaluation of Alternative Chain Pillar Designs in a Deep Longwall Mine - SME Annual Meeting 2025 - Zoheir Khademian; Daniel Su; Mark Van Dyke; Steve Hicks; Mark Mazzella; Nicole Evanek; Yuting Xue; Todd Minoski (Society for Mining, Metallurgy & Exploration, 2025)
Design of chain pillars in a longwall mine setting is one of the main engineering controls on the global and local stability of the mine. Challenges with roof instabilities, floor heaves, and pillar failures can be alleviated, to some extent, by careful design of gateroad configurations and chain pillars. This work investigates three different alternative designs in a three-entry-system gateroad configuration with an inter-panel barrier in a longwall mine in Virginia. Starting with the current design, which has faced challenges such as excessive floor heave, a geomechanical model developed in 3DEC software is validated by monitoring in-situ pillar stress in the yield, abutment, and barrier pillars in the mine. Next, three different chain pillar designs are evaluated in the model with a focus on roof sagging, floor heave, and pillar average stress. Results show the relationships among the alternative designs and instabilities associated with roof, pillar, and floor in the study mine, providing insights for optimizing longwall mining designs in deep-cover settings.